Feminist Theories and Migration Research-Making Sense in the Data Feast? - Altamirano, Aina Tollefsen (Refuge: Canada’s Journal on Refugees, 1997)
Conceptual and theoretical issues are increasingly highlighted in research on international migration. This article looks at some recent developments within feminist geography and questions whether feminist theories can contribute to the understanding of international migration. Three main traditions are identified within feminist geography found in recent work on gender and migration. The conclusion is that migration research can benefit from feminist empiricism through detailed documentation and measurement of gendered migration streams, while the essentialism of anti-rationalist feminism could lead to over-generalizations in terms of male and female mobility. Post-rational feminist approaches to migration research could contribute to studies of subgroups of migrants (both women and men) and their relational position in diferent contexts.